A STUDY OF MIND MAPPING COLLABORATIVE WRITING TECHNIQUES FOR TEACHING WRITING DESCRIPTIVE TEXTS - Sijono Sijono (VOX EDUKASI: Jurnal Ilmiah Ilmu Pendidikan, 2018)
This research aimed to improve students’ ability in writing descriptive text through mind mapping collaborative writing technique. The data were taken from students of A1 in English Study Program of STKIP Persada Khatulistiwa Sintang in the Academic Year 2017-2018. The finding showed that this technique could make the students enjoyed the writing activity and generated the students’ motivation to get involved in the writing process. The students were happy worked collaboratively with other student; moreover, the students could share their difficulties among the activity. Mind mapping collaborative writing could help the students to improve their writing descriptive texts and motivate the students to be active in the writing activity. Mind mapping collaborative writing is suggested to use in teaching writing at any level of the studentsand for any kind of texts. Keywords: Teaching Writing, Mind Mapping Collaborative Writing, Writing Descriptive Texts.